Transformation of QRIS-Based Charity Boxes: Philanthropy as a Sustainable Innovation for Islamic Da’wah in the Digital Era - Kahfi, Al; Kori, Ahmat; Oktaviani, Yeyen; Malintang, Jimmy; Qonitah, Mona (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2025)
This study aims to analyze the role of the Quick Response Code Indonesian Standard (QRIS) in supporting the sustainability of Islamic da’wah through the digitalization of charity boxes. The transformation of digital philanthropy has brought significant changes to donation practices, including the management of QRIS-based charity boxes. This innovation enables the community to contribute to Islamic da’wah in a simpler, more efficient, and transparent manner. Using a qualitative approach based on literature review, this research highlights aspects of accessibility, transparency, efficiency in fund distribution, and technology-based da’wah innovation. The findings show that the use of QRIS not only improves the efficiency of fund management but also strengthens the accountability of da’wah institutions through real-time transaction recording. Furthermore, the integration of QRIS with other technologies such as blockchain and Sharia fintech has the potential to expand the reach of da’wah and create a more sustainable philanthropic ecosystem. These findings suggest that digital technology is not merely a tool but a new foundation in contemporary da’wah strategies. Therefore, the adoption of this technology becomes a strategic step in addressing the challenges of da’wah in the digital era, while simultaneously enhancing awareness and community involvement in sharing for the common good. This study recommends strengthening digital literacy and technology governance as follow-up measures to enhance the impact of digital philanthropy for Islamic da’wah. Abstrak: Penelitian ini bertujuan untuk menganalisis peran Quick Response Code Indonesian Standard (QRIS) dalam mendukung keberlanjutan dakwah melalui digitalisasi kotak amal. Transformasi filantropi digital telah membawa perubahan signifikan dalam praktik donasi, termasuk dalam pengelolaan kotak amal berbasis QRIS. Inovasi ini memungkinkan masyarakat untuk berkontribusi dalam dakwah Islam dengan cara yang lebih mudah, efisien, dan transparan. Dengan pendekatan kualitatif berbasis studi pustaka, penelitian ini menyoroti aspek kemudahan akses, transparansi, efisiensi distribusi dana, serta inovasi dakwah berbasis teknologi. Hasil penelitian menunjukkan bahwa penggunaan QRIS tidak hanya meningkatkan efisiensi pengelolaan dana, tetapi juga memperkuat akuntabilitas lembaga dakwah melalui pencatatan transaksi secara real-time. Selain itu, integrasi QRIS dengan teknologi lain seperti blockchain dan fintech syariah berpotensi memperluas cakupan dakwah dan menciptakan ekosistem filantropi yang lebih berkelanjutan. Temuan ini mengindikasikan bahwa teknologi digital tidak hanya menjadi alat bantu, tetapi fondasi baru dalam strategi dakwah kontemporer. Oleh karena itu, adopsi teknologi ini menjadi langkah strategis dalam menjawab tantangan dakwah di era digital, sekaligus meningkatkan kesadaran dan keterlibatan umat dalam berbagi untuk kemaslahatan bersama. Penelitian ini merekomendasikan penguatan literasi digital dan tata kelola teknologi sebagai langkah lanjut dalam memperkuat dampak filantropi digital bagi dakwah Islam.